Bioethanol production from rice straw through an enzymatic route mediated by enzymes developed in-house from Aspergillus fumigatus - Jin, Xianchun; Song, Jianing; Liu, Gao-Qiang (Energy (Oxford), 2020)
This study concerns the in-house development of enzymes from Aspergillus fumigatus and their application in separate hydrolysis and fermentation (SHF) processes for bioethanol production from pretreated rice straw. The cellulase and hemicellulase activities of A. fumigatus cultivated in NaOH-pretreated rice straw were much higher than those of A. fumigatus cultivated in raw rice straw. A. fumigatus cultivated in raw rice straw exhibited no lignin-degrading manganese peroxidase (MnP) or laccase enzymatic activity. However, A. fumigatus cultivated in NaOH-pretreated rice straw exhibited high lignin-degrading MnP and laccase enzymatic activity. A. fumigatus completely degraded 1.0% NaOH-pretreated rice straw, yielding 27.89 g/L reducing sugar upon loading of 50 g/L rice straw (based on the original amount of rice straw that went to pretreatment). Saccharification of 1.0% NaOH-pretreated rice straw using 200 FPU/mL crude enzyme released 22.15 g/L reducing sugars in 20 h. The SHF processes resulted in an ethanol concentration and yield of 9.45 g/L and 83.5%, respectively, with Saccharomyces tanninophilus. •Aspergillus fumigatus produces all the enzyme components required for biomass hydrolysis.•A. fumigatus enzymes were evaluated for application in SHF for bioethanol production.•The SHF processes resulted in an ethanol concentration and yield of 9.45 g/L and 83.5%, respectively.•Bioethanol can be obtained efficiently and inexpensively with addition of only 10 g/L (NH4)2SO4.•Lignin-degrading enzymes are very important for reducing sugar and bioethanol production.